Germ-Free Mice Exhibit Mast Cells With Impaired Functionality and Gut Homing and Do Not Develop Food Allergy - Schwarzer, Martin; Hermanova, Petra; Srutkova, Dagmar; Golias, Jaroslav; Hudcovic, Tomas; Zwicker, Christian; Sinkora, Marek; Akgün, Johnnie; Wiedermann, Ursula; Tuckova, Ludmila; Kozakova, Hana; Schabussova, Irma (Frontiers in Immunology, 2019)
Background: Mucosal mast cells (MC) are key players in IgE-mediated food allergy (FA). The evidence on the interaction between gut microbiota, MC and susceptibility to FA is contradictory. Objective: We tested the hypothesis that commensal bacteria are essential for MC migration to the gut and their maturation impacting the susceptibility to FA. Methods: The development and severity of FA symptoms was studied in sensitized germ-free (GF), conventional (CV) and mice mono-colonized with L. plantarum WCFS1 or co-housed with CV mice. MC were phenotypically and functionally characterized. Results: Systemic sensitization and oral challenge of GF mice with ovalbumin led to increased levels of specific IgE in serum compared to CV mice. Remarkably, despite the high levels of sensitization, GF mice did not develop diarrhea or anaphylactic hypothermia, common symptoms of FA. In the gut, GF mice expressed low levels of the MC tissue-homing markers CXCL1 and CXCL2 and harbored fewer MC which exhibited lower levels of MC protease-1 after challenge. Additionally, MC in GF mice were less mature as confirmed by flow-cytometry and reduced edema formation after injection of degranulation-provoking compound 48/80. Co-housing of GF mice with CV mice fully restored their susceptibility to develop FA. However, this did not occur when GF mice were mono-colonized with L. plantarum. Conclusion: Our results demonstrate that microbiota-induced maturation and gut-homing of MC is a critical step for the development of symptoms of experimental FA. This new mechanistic insight into microbiota-MC-FA axis can be exploited in the prevention and treatment of FA in humans.